Happiness in the air: How does a dirty sky affect mental health and subjective well-being? - Zhang, Xin; Zhang, Xiaobo; Chen, Xi (Journal of environmental economics and management, 2017)
Previous studies evaluating the welfare cost of air pollution have not paid much attention to its potential effect on mental health and subjective well-being (SWB). This paper attempts to fill the gap by investigating the impact of air pollution on several key dimensions, including mental health status, depressive symptoms, moment-to-moment happiness, and evaluative happiness. We match a nationwide longitudinal survey in China with local air quality and rich weather conditions according to the exact time and place of survey. By making use of variations in exposure to air pollution for the same individuals over time, we show that air pollution reduces hedonic happiness and increases the rate of depressive symptoms, while life satisfaction has little to do with the immediate air quality. Our results shed light on air pollution as an important contributor to the Easterlin paradox that economic growth may not bring more happiness.